Somatostatin-SSTR3-GSK3 modulates human T-cell responses by inhibiting OXPHOS - Zhang, Bo; Feng, Huiru; Lin, Hui; Li, Rui (Frontiers in Immunology, 2024)
Somatostatin (SST) is a peptide hormone primarily synthesized in the digestive and nervous systems. While its impact on the endocrine system is well-established, accumulating evidence suggests a crucial role for SST and its analogues in modulating immune responses. Despite this, the precise mechanism through which SST regulates T cells has remained largely unknown. In our study, we explored the effects of SST on human T cells and discovered that it diminishes T-cell proliferation by influencing IL-2 production and T-cell mitochondrial respiration, while having no discernible impact on TCR-induced glycolysis. Our findings also identified that the regulatory influence of SST on T-cell responses and metabolism is contingent on its receptor, SSTR3. Moreover, we demonstrated that SST governs T-cell responses and metabolism by acting through the T-cell metabolic checkpoint GSK3. Collectively, our data provides molecular insights into the immunoregulatory function of SST in human T cells.